ENANTIOSELECTIVITY OF ISOLATE LIPASE FROM THE METAGENOM APPROACH TO (R,S)- MANDELIC ACID IN TRANSESTERIFICATION REACTIONS - Fatmawati, Fenti
LK1, LK2, and LK3 are lipase genes obtained from the metagenome of compost samples. The gene that encodes this lipase has been stored in GenBank with access numbers KP204883, KP204884, and KP204885 respectively. Lipase gene expression LK1, LK2, and LK3 in the pET30a(+) expression vector in Eschericia coli hosts induced by IPTG was carried out to obtain recombinant protein lipase.